2015
DOI: 10.5056/jnm14114
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Abdominal Visceral Fat, Circulating Inflammatory Cytokines, and Leptin Levels on Reflux Esophagitis

Abstract: Background/AimsAlthough adipocytes secrete inflammatory cytokines and adipokines, their role in reflux esophagitis is controversial. We investigated the association between visceral fat and inflammatory cytokines or adipokines in reflux esophagitis. MethodsAbdominal visceral fat and cytokines were measured in 66 individuals with reflux esophagitis and 66 age-and sex-matched controls. The mean values for visceral fat and cytokines were compared in cases and controls. Second, correlations between visceral fat an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 28 publications
0
31
3
Order By: Relevance
“…who announced that a diminished level of adiponectin was found in a patient with severe GERD assessed by video esophagography. In contrast to our study, a study by Nam et al 15. showed that adiponectin had no overall relationship with reflux esophagitis.…”
Section: Discussioncontrasting
confidence: 99%
“…who announced that a diminished level of adiponectin was found in a patient with severe GERD assessed by video esophagography. In contrast to our study, a study by Nam et al 15. showed that adiponectin had no overall relationship with reflux esophagitis.…”
Section: Discussioncontrasting
confidence: 99%
“…Several population‐based studies and meta‐analyses have reported that general obesity, expressed by elevated body mass index (BMI) is one of the important risk factors for developing GERD symptoms and endoscopically diagnosed erosive esophagitis. Recently, abdominal obesity, which is typically measured in terms of waist circumference (WC), has also been revealed as independent risk factor . Thus, recent studies have investigated the association between changes in weight or WC and GERD, and have shown that weight gain or increase in WC is positively associated with the development of GERD symptoms or erosive esophagitis .…”
Section: Introductionmentioning
confidence: 99%
“…7,16,17,58 A male-predominant gender bias including reflux esophagitis, BE, and EAC allude to sex and gender differences in the vulnerability or resistance of the esophageal epithelium to caustic compounds of gastroduodenal contents. 16,59 Decreased estrogen after menopause might be related with the rise in the incidence and severity of reflux esophagitis (Fig.…”
Section: Role Of Estrogenmentioning
confidence: 99%